2014
DOI: 10.1097/nmd.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Montreal Assessment of Need Questionnaire for Community Mental Health Planning

Abstract: Needs assessment facilitates mental health services planning, provision, and evaluation. This study aimed to a) validate a new instrument, the Montreal Assessment of Needs Questionnaire (MANQ), and b) use this to assess variations and predictors of need (number and seriousness) in 297 individuals with severe mental disorders for 18 months, during implementation of the Quebec Mental Health Action Plan. MANQ internal and external validations were adequate. Variables significantly associated with need number and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
(99 reference statements)
0
15
0
2
Order By: Relevance
“…The validation of the MANQ was the subject of a previous publication. 43 Participants answered all questionnaires except for the MCAS, which case managers completed. Participants' medical records provided complementary clinical data: DSM-IV diagnoses (4 axes), history of suicide attempt and suicidal ideation, number of previous suicide attempts, history of violence, and history of legal problems.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…The validation of the MANQ was the subject of a previous publication. 43 Participants answered all questionnaires except for the MCAS, which case managers completed. Participants' medical records provided complementary clinical data: DSM-IV diagnoses (4 axes), history of suicide attempt and suicidal ideation, number of previous suicide attempts, history of violence, and history of legal problems.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Researchers studying ''unmet needs'' have found that people whose needs go unmet tend to be older (Hansson et al 1995;Middleboe et al 2001) and male (Kulhara et al 2010;Ochoa et al 2003); they have multiple mental disorders (Baksheev et al 2010;Hansson et al 1995), as well as cooccurring drug or alcohol abuse (Baksheev et al 2010;Tremblay et al 2014) They may also experience low quality of life (Bengtsson-Tops and Hansson 1999;Slade et al 2004;Van Busschbach and Wiersma 2002), little social support (Wiersma and van Busschbach 2001), and trouble functioning in the community (Ochoa et al 2003;Slade et al 1999). These patients also consult fewer professionals (Gallagher and Teesson 2000;Lasalvia et al 2000).…”
Section: Introductionmentioning
confidence: 95%
“…the patient is receiving inadequate support). That is, no distinction is made between a ''serious need'' and the patient's perception of inadequate care, which could lead to misleading study results (Fleury et al 2013;Tremblay et al 2014). Yet some types of help may possibly be adequate for certain needs, which are only apparently ''unmet.''…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For community-residing individuals with dementia, family caregivers account for the largest share of care provision and often become the source of information on unmet needs. The tasks of dementia caregivers encompass all domains from assisting with daily activities to making decisions on economic and health-care issues [11].…”
Section: Introductionmentioning
confidence: 99%